2015
DOI: 10.7860/jcdr/2015/11125.5645
|View full text |Cite
|
Sign up to set email alerts
|

Giant Serpentine Vertebrobasilar Aneurysm with Vertebral Artery Hypoplasia and Fenestration- A Case Report

Abstract: Intracranial aneurysm in paediatric age group is rare and association of the aneurysm with congenital vertebral artery anomaly is further rarer. We describe such a case in an 11-year-old male patient who consulted a paediatrician about headache and vertigo, and a noncontrast CT (NCCT) head revealed peripherally calcified hyperdense mass in prepontine and basal cisterns. Magnetic resonance imaging (MRI) including contrast enhanced magnetic resonance angiography (MRA) revealed partially thrombosed giant serpenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…20 VA atresia is also associated with complex VA aneurysms. 21 However, in our series, VA atresia was not associated with a higher incidence among patients with VA-PICA aneurysms.…”
Section: Discussioncontrasting
confidence: 67%
“…20 VA atresia is also associated with complex VA aneurysms. 21 However, in our series, VA atresia was not associated with a higher incidence among patients with VA-PICA aneurysms.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the drawback of DSA is that the aneurysm wall is not visible 27 . The diagnostic accuracy for SA by magnetic resonance angiography (MRA) is similar to that obtained by CTA 3 , 34 .…”
Section: Imaging Examinationmentioning
confidence: 64%
“…SAs are more common in adults. Our literature review located several reported cases in children, and some of these cases may have been associated with arterial developmental abnormalities 3 .…”
Section: Introductionmentioning
confidence: 99%
“…CT angiography and MRI can be performed to screen for GSA and perfusion CT can clearly indicate the ischemic changes occurring in brain tissue around aneurysms. In this patient, MRI clearly demonstrates the mass effect, perivascular enhancement, and hypointense flow void representing the patent channel within the aneurysm [10].…”
Section: Discussionmentioning
confidence: 79%